2013
DOI: 10.7567/jjap.52.05da12
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Gas Permeation Characteristics of Ultrahigh Barrier Edge Sealing Materials from Asymptotic Solution of Diffusion Equation

Abstract: Materials and structures for water vapor barrier sealing are now actively studied, as the commercialization of organic electronic devices has become a reality. In this paper, we focus on the edge sealing barriers, in which diffusion plays an essential role. In the past, the diffusionlimited gas barrier properties were analyzed in the steady-state approximation, which is never reached within the device lifetime in the application for organic electronics. We analyze them using a simple analytical model. The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Therefore we consider this saturation period is required for the sample to reach the stationary condition in terms of the H 2 O concentration distribution across the film thickness. As we have analyzed by using the diffusion equation [5], the distribution of H 2 O molecules across the film thickness starts from the saturation value at one side facing to the H 2 O vapor, and that at the other side is completely dry. From the diffusion constant of H 2 O in polymers, it is reasonable that the stationary condition is achieved after several P-126 / Y. Nakano days.…”
Section: Limiting Factors Of Measurement Timementioning
confidence: 99%
“…Therefore we consider this saturation period is required for the sample to reach the stationary condition in terms of the H 2 O concentration distribution across the film thickness. As we have analyzed by using the diffusion equation [5], the distribution of H 2 O molecules across the film thickness starts from the saturation value at one side facing to the H 2 O vapor, and that at the other side is completely dry. From the diffusion constant of H 2 O in polymers, it is reasonable that the stationary condition is achieved after several P-126 / Y. Nakano days.…”
Section: Limiting Factors Of Measurement Timementioning
confidence: 99%
“…The criterion for the water vapor barrier is very severe in OLEDs (10 −6 g m −2 day −1 level) [1], while they are less severe in other thin film devices (TFTs and solar cells) and thick film devices (LCDs and batteries). There are various methods to detect water vapor transmission rate (WVTR) for film substrate materials and coatings: the calcium test method [5][6][7], differential pressure measurement [8], mass spectrometry [9], mass spectroscopy with a cold trap [10][11][12], electrochemical detection [13], highly sensitive optical absorption using cavity ringdown [8,14], etc. We have found that the adsorption of water molecules on the instrumental wall gives the deviating background by temperature fluctuation [12], and a method that uses chemical reactions, such as the calcium test, has an advantage for reducing the instrument sizes and, thus, the effect of wall outgasses.…”
Section: Introductionmentioning
confidence: 99%